The difference in leaves production, protein and calcium of Moringa oleifera under modification planting media, application of PGR and nitrogen - SULISTIANI, RINI; YUSUF, MUKHTAR; SARAGIH, SYAIFUL AMRI (Universitas Syiah Kuala, 2024)
Moringa has many ingredients of nutrients that are beneficial for food sources and nutrients that have not been widely cultivated. The nutritional content, benefits and high demand for Moringa abroad will open large opportunities for exporting Moringa flour. Foods full of nutrition will support the maintenance of good public health. For this reason, it is necessary to study and research cultivation techniques that produce high Moringa leaves and can be available sustainably. Production of Moringa leaves as a source of secondary metabolites can be increased by modifying the planting media and applying Plant Growth Regulator (PGR) and Nitrogen. The study used Split Split Plot Design with the main plot immersion by PGR, consisting of 3 types, namely: G1 (Fresh water), G2 (Coconut water), and G3 (GA3). The subplot was the treatment of planting media with two types: M (soil: sand: manure = 1:1:2); M (soil: sand: manure = 1:2:1). The sub subplots were N (urea) fertilizer, with four levels: N0 (0 g/plant); N1 (5 g/plant); N (10 g/plant); and N (15 g/plant). Each treatment combination goes over three times. The agronomic parameters observed were plant height, the number of leaves, fresh crop weight, and root volume, and the biochemical parameters observed were chlorophyll, protein, and calcium levels. The composition of the planting media caused significant differences in plant height at 4, 6, and 10 weeks after planting (WAP), the number of leaves at 4 WAP, and root length at 10 WAP. Growth Regulators significantly affected plant height at 4, 6, and 10 WAP, the number of leaves at 4 WAP, and root length at harvest. Nitrogen fertilization caused significant differences in plant height at 4, 6, and 10 WAP, volume, and root length at harvest (10 WAP). The combination of Planting media, PGR, and Nitrogen treatments caused significant differences in plant height at 4, 6, and 10 WAP and the number of leaves at 6 WAP. Laboratory analysis in this study showed high calcium and protein in Moringa leaves.